2010
DOI: 10.3390/mca15010001
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Wheat and Barley Stems and Design of New Beam/Columns

Abstract: In this study, physical and mechanical properties of wheat and barley stems are examined. Transverse sections of the stems are magnified by a microscope and the material structure in the transverse sections are analysed with image processing programs. Geometric properties such as inner, outer radius, stem wall thickness and density variation of the material along the radius are measured and density variations are approximated by a mathematical model. Moment of inertia of the cross-sectional area which plays a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Interestingly, they demonstrated that bending tests can be used to estimate the cell wall thickness and that a core ring structure, with a cellular core of lower density than the outer shell, can significantly increase the bending resistance of plant stems. Similar conclusions were obtained by Deger et al thanks to numerical modelling [354]. These kinds of structures are similar to the structure of a flax stem and offer explanation for the extraordinary length to diameter ratio of this plant (Figure 12).…”
Section: Mechanical Characterisation Of Plant Stemssupporting
confidence: 88%
“…Interestingly, they demonstrated that bending tests can be used to estimate the cell wall thickness and that a core ring structure, with a cellular core of lower density than the outer shell, can significantly increase the bending resistance of plant stems. Similar conclusions were obtained by Deger et al thanks to numerical modelling [354]. These kinds of structures are similar to the structure of a flax stem and offer explanation for the extraordinary length to diameter ratio of this plant (Figure 12).…”
Section: Mechanical Characterisation Of Plant Stemssupporting
confidence: 88%
“…In addition, pig C had the highest UniFrac distance and IQR indicating large variation between DNA extracted from FAS and POW . The major components in diet fed to pig C are barley fines which are physically more granular and abrasive than wheat fines [ 39 ], and thus possibly contribute to additional physical shear in addition to the extraction method.…”
Section: Resultsmentioning
confidence: 99%